A mid-Cretaceous angiosperm-dominated macroflora from the Cedar Mountain Formation of Utah, USA. (27th July 2016) - Harris, Elisha B.; Arens, Nan Crystal
Abstract: Angiosperms first appeared in the fossil record as pollen during the Valanginian–Hauterivian; they spread out of the tropics in the Aptian and Albian, and radiated in the Late Cretaceous. Despite these general patterns, details of the taxonomic, geographic, and ecological evolution of Cretaceous angiosperms are relatively poorly known because only a handful of Early and mid-Cretaceous macrofloras have been reported. This is the first detailed report of a fossil leaf flora from the Cedar Mountain Formation from the mid-Cretaceous of the Western Interior. We describe a flora that is overwhelmingly dominated by angiosperms (152 of 153 identified specimens are angiosperms) from the Albian–Cenomanian transition that is preserved in a clay- and carbonate-rich, lacustrine mudstone from the uppermost Cedar Mountain Formation of Emery County, Utah. We recognize 18 leaf morphotypes, all of which are dicotyledonous angiosperms. The majority of the Cedar Mountain morphotypes have taxonomic affinities with forms of similar age described from the Atlantic and Gulf coastal plains and other localities from the Western Interior. From this, we infer that a relatively diverse angiosperm flora grew along the margins of a small pond on the coastal plain. Palynological preparations of the fossil matrix were barren; however, previous studies of other facies within the formation showed that both conifers and ferns were important components of the regional vegetation during Cedar Mountain time. The effective absence of conifers and ferns in this macroflora and low leaf mass per area values among the angiosperms measured suggests that even at the Early–Late Cretaceous transition, angiosperms had come to dominate some sites, particularly those that were disturbed or seasonally ephemeral, where fast-growth or seasonal deciduousness would have been favored.